Internationalisation Of The Housing Development Sector: A Study Of The Malaysian Scenario - Awil, Ahmed Usman (2007)
Structural changes in economies, reforms in the housing sector and increasing urbanisation rates has both increased the demand for the housing and created potential opportunities for housing developers. The housing sector has recently been experiencing increasing activities by firms undertaking housing development activities away from home markets. This study aims to examine the internationalisation of housing developers from Malaysia. The purpose of this study was to find the present export capabilities of Malaysian housing developers and to investigate and understand those Significant factors that enable them to be competitive internationally. Additionally, this study aims to test whether the theories of internationalisation are applicable in the context of the housing development sector. This study targeted a sample of internationally experienced Malaysian housing developers through a two-stage mixed methodology approach. The findings of this study argue that Malaysian housing developers were helped both by their internally generated ownership advantages and ownership advantages accrued by virtue of their Malaysian ownership, It was found that theories of internationalisation were applicable to the housing sector, but, the role of government and chance events to have played an important role in directing the location and the pace of their internationalisation. Additionally, the findings of this study point to the critical role of the decision-makers, who we term as "pioneer-entrepreneurs." We found no support for Malaysian housing developers internationalising based on cultural or linguistic affinities. Based upon the study findings, theoretical and practical implications for the housing sector are discussed and suggestions made for future research.